Theatre and science, with specific reference to Shelagh Stephenson's An experiment with an air pump (1999) - Van Niekerk, Dion (Rhodes University, Faculty of Humanities, Department of Drama, 2002)
Science has featured intermittently as the subject of theatrical texts since Thomas Shadwell first represented the Renaissance scientist in The Virtuoso (1676). The late twentieth century, however, saw an incremental growth in theatre's interest in scientific exploration, a growth concommitant with the vast impact that science has had on technology, warfare and the machinations of political power. The tensions generated by the disjuncture between the rationality of science and the unpredictability of human society have provided a rich source of material for theatrical investigation into the human experience. The purpose of this thesis is twofold: to reveal some of the thematic concerns that emerge in this genre, and to examine the interplay between theatre and science. Shelagh Stephenson's An Experiment with an Air Pump (1999) provides a useful point of focus for this inquiry. By parallelling two time periods, exposing the scientific objectification of women and, in addition, opening up contemporary ethics for negotiation with the audience, Stephenson calls into question the objectivity and certainty of history, gender and ethical conduct. These she presents as dynamic and evolving fields of discourse that contribute to, but do not solely constitute, knowledge and understanding of the world. An Experiment with an Air Pump also displays an awareness, through its metatheatricality, of theatre itself as an imaginative, subjective discourse which parallels the more intuitive and personal aspects of scientific exploration. The play functions as a microscope, bringing into focus a contemporary world in which traditional systems of understanding and knowledge need to be reassessed and reinvented.
Keywords: Science in literature; Stephenson, Shelagh -- Experiment with an air pump